Pyocin-mediated antagonistic interactions in Pseudomonas spp. isolated in James Ross Island, Antarctica - Snopková, Kateřina; Dufková, Kristýna; Chamrád, Ivo; Lenobel, René; Čejková, Darina; Kosina, Marcel; Hrala, Matěj; Holá, Veronika; Sedláček, Ivo; Šmajs, David (Environmental microbiology, 2022)
Interactions within bacterial communities are frequently mediated by the production of antimicrobial agents. Despite the increasing interest in research of new antimicrobials, studies describing antagonistic interactions among cold-adapted microorganisms are still rare. Our study assessed the antimicrobial interactions of 36 Antarctic Pseudomonas spp. and described the genetic background of these interactions in selected strains. The overall bacteriocinogeny was greater compared to mesophilic Pseudomonas non-aeruginosa species. R-type tailocins were detected on transmission electron micrographs in 16 strains (44.4%); phylogenetic analysis of the corresponding gene clusters revealed that the P. prosekii CCM 8878 tailocin was related to the Rp3 group, whereas the tailocin in Pseudomonas sp. CCM 8880 to the Rp4 group. Soluble antimicrobials were produced by eight strains (22.-2%); gene mining found pyocin L homologues in the genomes of P. prosekii CCM 8881 and CCM 8879 and pyocin S9-like homologues in P. prosekii CCM 8881 and Pseudomonas sp. CCM 8880. Analysis of secretomes confirmed the production of all S- and L-type pyocin genes. Our results suggest that bacteriocin-based inhibition plays an important role in interactions among Antarctic soil bacteria, and these native, cold-adapted microorganisms could be a promising source of new antimicrobials.
Keywords: bakteriociny; Antarctic Regions; Bacteriocins; Pyocins; Pseudomonas; Phylogeny; fylogeneze; Pseudomonas aeruginosa; pyociny; Antarktida